TAX EXPENDITURES AS AN INCENTIVE FOR THE AGRICULTURE IN BULGARIA - Nadezhda BLAGOEVA; Vania GEORGIEVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The government can use different ways to stimulate certain industries or categories of taxpayers. It can be achieved with direct payments and subsidies that increase the budget revenues. It is also possible to achieve this aim by reducing budget revenues by failing to collect some of them to be ceded to preferred groups of taxpayers. These are so-called tax expenditures. In Bulgaria, official statistics on their value and impact have been kept since 2007. Following the requirements of the EU, a national definition of the term tax expenditure is adopted in Bulgaria, which should correspond to the specifics of our tax system. Despite the relatively small share of the tax expenditures - about 2% of total tax revenues in Bulgaria, their values are subject to continuous analysis and control of their effectiveness. The lower it is, the state fails to collect additional revenues without generating benefits for the economy. At the same time, how our tax policy can use them to stimulate an industry such as agriculture, where employment is still quite high, is a priority of this study. The purpose of this article is to assess and analyze the tax expenditures applicable for agriculture in Bulgaria. Modern approaches and methods such as the method of analysis and synthesis have been used in solving the research tasks and achieving the main goal in the research; inductive and deductive methods, comparative methods, and logical description. Continuous analysis and assessment of each tax preference and relief are necessary to be made to establish their effectiveness. This also concerns tax expenditures. If they are ineffective, the state simply fails to collect additional budget revenues without creating benefits for society and the economy The tax legislation in Bulgaria provides for the application of a small number of tax revenues due to its broad tax base and low tax rates. However, a significant part of them is intended for agriculture. It can be concluded that along with tourism, agriculture enjoys the most tax reliefs.